Transcriptomic changes during stage progression of mycosis fungoides. (1st March 2022) - Xiao, M.Z.X.; Hennessey, D.; Iyer, A.; O'Keefe, S.; Zhang, F.; Sivanand, A.; Gniadecki, R.
Summary: Background: Mycosis fungoides (MF) is the most common cutaneous T‐cell lymphoma, which in the early patch/plaque stages runs an indolent course. However, 25% of patients with MF develop skin tumours, a hallmark of progression to the advanced stage, which is associated with high mortality. The mechanisms involved in stage progression are poorly elucidated. Objectives: We sought to address the hypothesis of MF cell trafficking between skin lesions by comparing transcriptomic profiles of skin samples in different clinical stages of MF. Methods: We performed whole‐transcriptome and whole‐exome sequencing of malignant MF cells from skin biopsies obtained by laser‐capture microdissection. We compared three types of MF lesions: early‐stage plaques (ESP, n = 12) as well as plaques and tumours from patients in late‐stage disease [late‐stage plaques (LSP, n = 10) and tumours (TMR, n = 15)]. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were used to determine pathway changes specific for different lesions which were linked to the recurrent somatic mutations overrepresented in MF tumours. Results: The key upregulated pathways during stage progression were those related to cell proliferation and survival (MEK/ERK, Akt‐mTOR), T helper cell (Th)2/Th9 signalling [interleukin (IL)4, STAT3, STAT5, STAT6], meiomitosis (CT45A1, CT45A3, STAG3, GTSF1, REC8) and DNA repair (PARP1, MYCN, OGG1). Principal coordinate clustering of the transcriptome revealed extensive gene expression differences between early (ESP) and advanced‐stage lesions (LSP and TMR). LSP and TMR showed remarkable similarities at the level of the transcriptome, which we interpreted as evidence of cell percolation between lesions via haematogenous self‐seeding. Conclusions: Stage progression in MF is associated with Th2/Th9 polarization of malignant cells, activation of proliferation, survival, as well as increased genomic instability. Global transcriptomic changes in multiple lesions may be caused by haematogenous cell percolation between discrete skin lesions.